Associação do estado nutricional e da saúde da gestante com a doação de leite materno - Larissa Bueno Ferreira (2016)
Introduction: The donation of human milk (HM) is necessary and plays a key role in neonatal outcomes, considering the benefits of HM; however, little attention is given to nursing mothers and their conditions of health and nutrition that can contribute to the donation. Objective: To identify the association of the nutritional status and health of the pregnant woman with HM donation in a human milk collection station (HMCS). Methods: Cross-sectional study with a secondary source of information, related to breastfeeding women candidates for HM donation in HMCS of a university hospital (2011-2014). Data were obtained sociodemographic, pregnancy, morbidities and laboratory records, as well as information on the HM donated: volume, number of donations and classification (colostrum, transitional and mature). Statistical analysis covered the Kolmogorov-Smirnov test, Spearman correlation, Chi-square, Mann-Whitney, Kruskal-Wallis, Wilcoxon and Fieldman. Results: 608 lactating women candidates were evaluated HM donation, most adults, with median: 24 years and 37 gestational weeks, and 85.8% were able to HM donation. It was identified that 27.2% of women were overweight in the pre-pregnancy period, increasing to 37.9% at the end of gestation (p<0.001). The excessive increase of weight favored morbidities during pregnancy (p=0.004). The pre-pregnancy BMI was correlated positive with age (r = 0.295, p <0.001), and negatively associated with weight gain (r =-0.144;p=0.005). Anaemia occurred 37.5% of the nursing mother's, while 77.3% reported use of ferrous sulfate. Already gestational age was associated inversely with the number of donations and total donated HM (r=-0.221 and r =-0.279; p<0.001, respectively). The median number of donations was one (0-17) and 92.5% of women have given up to three times. There was a higher prevalence of colostrum donation between adults and among non-anemic (p<0.005). Finally, changes were suggested in HMCS of care forms, study target in order to improve healthcare coverage and create opportunities future studies. Conclusion: HM donation was favored by the lower gestational age, being an adult and absence of anemia among mothers. These findings reinforce the need for better structuring in health care of women, focusing on the specific nutritional interventions and greater awareness of the breast-feeding and HM donation.